2016
DOI: 10.1038/srep22849
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle-enriched diamond-like carbon implant modification as a mammalian cell compatible surface with antimicrobial properties

Abstract: The implant-bone interface is the scene of competition between microorganisms and distinct types of tissue cells. In the past, various strategies have been followed to support bony integration and to prevent bacterial implant-associated infections. In the present study we investigated the biological properties of diamond-like carbon (DLC) surfaces containing silver nanoparticles. DLC is a promising material for the modification of medical implants providing high mechanical and chemical stability and a high deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Gorzelanny et al . () observed a fast and transient release of silver ions from diamond‐like carbon implants enriched in silver nanoparticles able to reduce the growth of S. aureus et S. epidermidis on the surface. They linked this release to the biocompatible behaviour of the implants, ensuring growth of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gorzelanny et al . () observed a fast and transient release of silver ions from diamond‐like carbon implants enriched in silver nanoparticles able to reduce the growth of S. aureus et S. epidermidis on the surface. They linked this release to the biocompatible behaviour of the implants, ensuring growth of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, surfaces with high concentrations of implanted ions showed high rates of dissolution into the surrounding medium even with nanoparticles (Furno et al 2004;Harrasser et al 2015). Gorzelanny et al (2016) observed a fast and transient release of silver ions from diamond-like carbon implants enriched in silver nanoparticles able to reduce the growth of S. aureus et S. epidermidis on the surface. They linked this release to the biocompatible behaviour of the implants, ensuring growth of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions, such as silver and copper, are one such set of antimicrobials that are currently of interest as they can be combined with functional materials for designing healthcare devices (Gorzelanny et al, 2016;Liu et al, 2016;Ramasamy and Lee, 2016;Sun et al, 2016;Bayramov and Neff, 2017). Whilst there is some evidence that bacteria can develop resistance mechanisms to certain forms of copper and silver (Percival et al, 2005;Santo et al, 2011;Finley et al, 2015;Hobman and Crossman, 2015;Williams et al, 2016), they are still promising as antimicrobials due to their broad ranges of biocidal activity against multiple microorganisms, including both Gram positive and Gram negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Adding non-carbide-forming elements like Ag [47,48], Cu [49], Al [50] and Ni [50] into the DLC matrix can reduce residual stress [43,45,[47][48][49][50] and improve electric conductivity [44,51]. Furthermore, copper-or silver-containing DLC thin films can show a significant antibacterial effect [52][53][54][55][56]. These composite coatings have been deposited by Arc evaporation with metal cathodes [57], magnetron sputtering [51], ion plating/sputtering [58], pulsed laser deposition [21,[59][60][61], laser ablation [62,63], plasma-immersion ion implantation [64], ion deposition [54], plasma-enhanced chemical vapor deposition (PECVD) [47] and variations thereof.…”
Section: Introductionmentioning
confidence: 99%